Risk of discontinuation of antipsychotic long‐acting injections vs. oral antipsychotics in real‐life prescribing practice: a community‐based study. (23rd March 2017) - Verdoux, H.; Pambrun, E.; Tournier, M.; Bezin, J.; Pariente, A.
Abstract : Objective: To compare the risk of discontinuation of ambulatory antipsychotic treatment in persons treated with antipsychotic long‐acting injections (LAIs) or by oral antipsychotics (OAPs). Methods: The study was performed in a representative sample of persons newly treated with OAPs ( n = 6904) affiliated to the French Insurance Healthcare system. The risk of all‐cause discontinuation was compared in patients prescribed OAPs ( n = 246) vs. matched patients prescribed LAIs ( n = 246) using multivariate survival analyses. Confounding by indication was minimized by matching on type of antipsychotic drug and by the high‐dimensional propensity score method. Results: Discontinuation was more frequent with OAPs (69%) compared to LAIs (57%) [adjusted relative risk (aRR) = 1.6, 95% CI 1.23–2.07]. Risk of discontinuation was higher for first‐generation (FGA) OAPs vs. FGA LAIs (aRR = 1.94, 95% CI 1.22–3.08) as well as for second‐generation (SGA) OAPs vs. SGA LAIs (aRR = 1.58, 95% CI 1.15–2.17). Over the 6‐month period after discontinuation of LAIs, a new antipsychotic drug was dispensed in 58% of patients, the most frequent pattern being dispensing of the same LAI as that prescribed before discontinuation. Conclusions: Although less frequent than with OAPs, the rate of ambulatory treatment discontinuation was high with LAIs. Prescription of LAIs should be associated with intervention strategies aimed at promoting medication adherence.